HR Planning Steps Based On Data From Job Analysis Results - Dian Evi Susanti; Desi Wiyanto; Derry Wahidaya (Indonesian Development of Economics and Administration Journal, 2022)
The purpose of this writing is to find out the steps of HR planning based on the results of job analysis based on the results of a literature study. This scientific article writing method uses literature studies / Library Research. Processing and analyzing reference sources of books, articles, journals, and other sources from the internet, especially within the scope of human resources (HR). HR planning steps begin with goal setting. It stated that organizations need to identify and define their objectives and prepare government documents including budget speeches and other required documents including strategic plans. This is important for understanding government regulations, deciding on an organization’s HR priorities and for coping with emerging environmental changes and trends. Then, carry out a workforce analysis to understand the workforce and plan about the required workforce (shortages and excess) with specific skills. and knowledge. There is a need to undergo a workforce analysis. Characteristics such as age, gender, skills, competence, etc. are very important to look at, also some internal factors such as eligibility criteria, vacancies, turnover rates, etc. are important to carry out a workforce analysis. Then do a gap analysis. Where companies are asked to have a success plan for critical positions and understand the importance of acquiring new skills. The next step is to decide HR priorities to help achieve goals. After looking at the results of the gap analysis, some HR priorities have to be decided and a strategy to achieve the desired results has to be developed and has to be recognized by the department. The final step is measuring, monitoring, and reporting progress. When evaluating the progress of a targeted area, monitoring, assessing and presenting HR performance results is essential. This leads to increased skills, and capabilities of employees and organizational learning to meet future needs and demands.